Afterlives of Revolution: Everyday Counterhistories in Southern Oman Alice Wilson (Stanford, CA: Stanford University Press, 2023). Pp. 336. $30.00 paper. ISBN: 9781503635784 - Lori, Noora (International Journal of Middle East Studies, 2025)
Keywords: Recension

La politica berbera nella Libia coloniale. Identità, reti e conflitti (1835-1924), Roma, Carocci, 2025, 166 pp. - Di Tolla, Anna Maria (Afriche e Orienti, 2026)
Keywords: Recension

Rive orientale de l'Arabie: hommes et espaces au début de l'islam / Moez Dridi. Éd. l'Harmattan, 2025 - Lochon, Christian (Mondes et Cultures : comptes rendus trimestriels des séances de l’Académie des sciences d’outre-mer, 2025)
Keywords: Recension

Contemporary Oman: The Sultan, the People, and the Legacy of Peace: By Mahjoob Zweiri and Farah AL Qawasmi (eds) (Berlin: Gerlach Press, 2025), viii + 263 pp., £90 (hardback), ISBN 978-3-95994-184-6 - Bradshaw, Tancred (Middle Eastern Studies, 2026)
Keywords: Recension

Oman’s Transformation after 1970 - Hughes, Geraint (Bustan: The Middle East Book Review, 2025)
Scholars and students of the history and politics of the Sultanate of Oman will in all likelihood acknowledge John E. Peterson as the doyen of their field, being active in the study of this Gulf state for just over fifty years. Oman’s Transformation after 1970 is a follow-up to his 2007 book Oman’s Insurgencies, which provided a detailed historical account of the Jebel Akhdar (1955–59) and Dhofar (1963–c.1976) rebellions and the counter-insurgency campaigns Sultans Said bin Taimur (1932–70) and Qaboos bin Said (1970–2020) waged with British support to defeat them.Over the past fifty-five years, Oman has evolved from an impoverished tribal state under Britain’s informal imperial influence to a fully sovereign, prosperous, but absolute monarchy. It has close ties to the Western powers and other members of the Gulf Co-operation Council (GCC), while playing an active role in regional diplomacy and preserving a semblance of neutrality (Oman has, for example, acted as a mediator between the US and the Islamic Republic of Iran and has tried to broker peace between the Houthis and their enemies in Yemen). Although the Sultanate did experience some internal unrest during the 2011 “Arab Spring” (442–44), it has not only emerged as one of the most stable states in the Middle East but also managed a peaceful transition of power after Qaboos’s death in January 2020. This was not an outcome that contemporary observers would have anticipated in the context of both Qaboos’s seizure of power in a palace coup in July 1970 or his regime’s struggle for survival against insurgent movements both in the Southern province of Dhofar and Northern Oman.1
Keywords: Recension

Afterlives of revolution: everyday counterhistories in southern Oman: by Alice Wilson, Stanford, CA, Stanford University Press, 2023, 336 pp., ISBN 978-1-5036-3578-4. - Alsraiha, Kassim (British Journal of Middle Eastern Studies, 2025)
Keywords: Recension

The Ottoman Ibadis of Cairo: A History by Paul M. Love Jr. (review) - Pierce, Stephen (African Studies Review, 2025)
Keywords: Recension

The Ottoman Ibadis of Cairo: A History by Paul M. Love Jr. (review) - Sabra, Adam (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies, 2025)
Keywords: Recension

Aillet, Cyrille. L’archipel ibadite. Une histoire des marges du Maghreb médiéval. Collection Mondes Médiévaux. Lyon: CIHAM-Éditions, 2022. ISBN: 9782956842644. 592 pp. €45 paper. - Bosanquet, Antonia (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2025)
Keywords: Recension

Amal Sachedina, Cultivating the Past, Living the Modern: The Politics of Time in the Sultanate of Oman:Cornell, Cornell University Press, 2021 274 pages - Ayachi, Mehdi (Critique internationale, 2025)
Keywords: Recension

Cyrille Aillet : L’archipel ibadite - une histoire des marges du Maghreb médiéval. - Hassen, Mohamed (Revue de l'Institut des Belles Lettres Arabes, 2024)
Keywords: Recension

Zanzibar was a Country: Exile and Citizenship between East Africa and the Gulf by Nathaniel Mathews (review) - Vartavarian, Mesrob (Global Black Thought, 2025)
Keywords: Recension

Cyrille Aillet, L’archipel ibadite. Une histoire des marges du Maghreb médiéval, CIHAM Éd., Lyon–Avignon, 2021 ; 1 vol., 582 p. (Mondes médiévaux, 5). ISBN : 978-2-95684-264-4. Prix : € 45,00 - Sénac, Philippe (Le Moyen Age, 2025)
Keywords: Recension

Britain and the Dhofar War in Oman, 1963–76: A covert war in Arabia: by Geraint Hughes, Basingstoke, Palgrave Macmillan, 2024, 325 pp, £119.99, ISBN 978-3-031-49498-7; The Dhofar War: British Covert campaigning in Arabia, 1965–75, by Stephen Quick, Exeter, University of Exeter Press, 2024, 235 pp, £95.00, ISBN 9781804130988. - Beckett, Ian F W (Small Wars & Insurgencies, 2025)
Keywords: Dhofar; Recension

Zanzibar Was a Country: Exile and Citizenship between East Africa and the Gulf By Nathaniel Mathews - Wint-Frederick, Hollian (Journal of Social History, 2025)
Tracing the lives, experiences, and ideas of Zanzibari Arabs through rich oral and written archives, Zanzibar Was a Country demonstrates the significance of “experiences in diaspora” to Indian Ocean postcolonial national belonging (2). Belonging, in Mathews’ rendering, refers to both “sentiment” —the idea of Zanzibar as a sovereign state and collective attachment to it—and citizenship—recognized political status and the infrastructures that produce it. The book makes two key intersecting interventions: first, by examining the political economy of citizenship from the era of developmental colonialism to the hydrocarbon-fueled developmentalism of the Arabian Gulf, Mathews presents an important analysis of decolonization as an economic process in which the tensions of the late colonial era continued. Second, he explores the complex and diverse articulations of Zanzibari-Omani belonging that emerged among diasporic Zanzibaris in this context, both in individual memory and through a vibrant vernacular historiography. This is a book that takes seriously not just the memories of its interlocutors, but their scholarship; their own endeavors in writing their history.
Keywords: Recension

Sovereigns of the Sea: Omani Ambition in the Age of Empire: by Seema Alavi - Chowdhary, Mir Kamruzzaman (Journal of the Indian Ocean Region, 2025)
Keywords: Recension

Hafed Abdouli, Min Trībūlīṭāniya ilā Aṭrābuls: al-mašhad al-ta‘mīrī ḫilāl al-‘aṣr al-wasīṭ al-mutaqaddam bayna al-tawāṣul wal-taḥawwulāt, [De la Tripolitaine à Tripoli : le paysage urbain au début du Moyen Âge entre continuité et changement]: Leyde, Brill, 2023 - Amara, Allaoua (Revue des mondes musulmans et de la Méditerranée, 2025)
Keywords: Recension

Zanzibar was a country: exile and citizenship between East Africa and the Gulf: Nathaniel Mathews, Oakland, CA, University of California Press, 2024, 358 pp., $29.95/£25.00 (paperback), ISBN: 9780520400702 - Nicholson, Timothy (Global Change, Peace & Security, 2025)
Keywords: Recension

Miranda Morris, Ethnographic Texts in the Baṭḥari Language of Oman - Rubin, Aaron D. (Journal of Semitic Studies, 2025)
Keywords: Linguistique -- Oman; Recension

Résistance et Dévotion. Anciens sanctuaires ibadites de Djerba - Chekhab-Abudaya, Mounia (Bulletin critique des Annales islamologiques, 2025)
Résistance et Dévotion : Anciens sanctuaires ibadites de Djerba, publié par Virginie Prevost, est le fruit d’un long travail commencé en 1996 et enrichi, depuis 2009, des clichés du photographe Axel Derriks. Cet ouvrage se présente comme une étude historique et architecturale minutieuse portant sur quarante-huit mosquées de l’île de Djerba, avec pour dessein de « conserver la mémoire des anciens lieux de culte de Djerba » (p. ix). Tout au long du volume, V. Prevost souligne de manière pertine...
Keywords: Architecture -- Djerba; Recension

Min Trībūlītānyā ilā Aṭrābulus : al-mashhad al-taʻmīrī khilāl al-ʻaṣr al-wasīṭ al-mutaqaddam bayn al-tawāṣul wa-l-taḥawwalāt من تريبوليتانيا إلى أطرابلس المشهد التعميري خلال العصر الوسيط المتقدّم بين التواصل والتحوّلات - Prevost, Virginie (Bulletin critique des Annales islamologiques, 2025)
Voici la première monographie publiée par le chercheur tunisien Hafed Abdouli, tirée en partie de sa thèse de doctorat consacrée à la Tripolitaine médiévale, défendue à Tunis en 2011 sous la direction de Faouzi Mahfoudh. L’ouvrage, préfacé par Ahmed M’Charek, constitue le premier volume d’une nouvelle collection des éditions Brill, Libya Islamica, et s’inscrit dans un intéressant programme de recherches dirigé par Aurélien Montel et Sébastien Garnier, Libmed, qui propose, sous la forme d’un s...
Keywords: Recension

Cultivating the Past, Living the Modern: The Politics of Time in the Sultanate of Oman: Amal Sachedina - Chatty, Dawn (Journal of Arabian Studies, 2025)
Keywords: Recension

في البدء كانت الفرق ...... وفي البدء كانت الإباضية .... عرض لكتاب" الفكر السياسي الإباضي : من خلال سير البرادي والشماخي وابن ذكوان الهلالي - البدوي, فوزي (Revue de l'Institut des Belles Lettres Arabes, 2015)
في البدء كانت الفرق ...... وفي البدء كانت الإباضية .... عرض لكتاب" الفكر السياسي الإباضي
Keywords: Recension

سردية الخرافة الشعبية الأمازيغية: قراءة في كتاب حكايات أمازيغية لفتحي بن معمر - ضو, سليم (Revue de l'Institut des Belles Lettres Arabes, 2023)
نهتمُّ في هذا المقال بدراسة لون من الأدب الشعبي هو الخرافة الشعبيّة الأمازيغيّة، وذلك بالبحث في بنيتها –أي الخرافة الشعبية- وخصائصها ومميزاتها التي بها تتفرّد عن سائر أنماط الأدب الشعبي الأخرى على غرار الأحاجي والأمثال وأغاني النساء... والنظر في القوانين التي من خلالها تنتظمُ، لغرض الوقوف على ملامح سرديّتها وأدبيّتها. وذلك من خلال تركيز النظر على مُدوّنة تونسيّة أثْرت بوضوح الأدب الشعبيّ التونسي، وأسهمت في نفض الغبار عن ثقافة محليّة مغمورة –نعني الثقافة الأمازيغيّة- يلفّها الكثير من النسيان والإغفال ويتهدّدها الاضمحلال جرّاء تراجع نسبة الناطقين بها لاعتبارات عديدة، ونقصدُ بذلك مجموعة "حكايات أمازيغيّة جربيّة" الكاتب التونسي من أصل أمازيغي فتحي بن معمر (1967). وتنخرطُ مجموعته هذه ضمن مشروع ثقافي كان قد انطلق فيه منذ سنوات يهدفُ إلى تجميع المادّة التراثية الأمازيغيّة الشفهيّة وتوثيقها ونشرها للتعريف بها لدى الأجيال الجديدة ولحمياتها من كل أشكال الطّمس والتغييب والسطو عليها. وسيكون تركيزنا خلال هذا المقال مُنصبًّا على فحص الخصائص الأجناسيّة لهذه النصوص ووظائفها، وذلك بالانطلاق بدراسة بنية هذه الحكايات الخارجيّة والداخليّة أي البنية القصصية المتكونة من اُطر وفواعل وأحداث، مرورا بالبحث في الشخصيات وأصنافها ووظائفها مستفيدين في ذلك من المنهج المورفولوجي لفلاديمير بروب، ثمّ التعريج على خصائص الأُطر الزمانية والمكانية، اِنتهاءً بالمواضيع والقضايا التي أثارتها هذه القصص. ثمّ في عُنصر لاحق لجأنا إلى رصد جُملة الوظائف التي تؤدّيها هذه الحكايات والتي منها ما يتعلّقُ بالراوي ومنها ما يتعلق بالمروي لهُ.
Keywords: Littérature -- Djerba; Recension

L'archipel ibadite - une histoire des marges du Maghreb médiéval - Mohamed, Hassane (Revue de l'Institut des Belles Lettres Arabes, 2024)
Keywords: Recension

Islam, réforme et colonisation: Une histoire de l’ibadisme en Algérie (1882-1962) - Cherih, Chaouki (Revue d'histoire moderne contemporaine, 2024)
Keywords: Recension

Alice Wilson, Afterlives of Revolution. Everyday Counterhistories in Southern Oman - Boulay, Sébastien (L’Homme. Revue française d’anthropologie, 2024)
Ce n’est pas la première fois qu’Alice Wilson nous invite à découvrir un mouvement révolutionnaire du monde arabo-musulman et ses réminiscences dans le présent. Notre collègue de l’Université de Sussex au Royaume-Uni s’était en effet déjà fait connaître en 2016 par un ouvrage consacré au mouvement de libération du Sahara occidental, le Front Polisario, et à la République arabe sahraouie démocratique, dans lequel elle se penchait sur la question de la souveraineté exercée par cet État exilé de...
Keywords: Recension

A Review of “Persistent Pastoralism: Monuments and Settlements in the Archaeology of Dhofar” - Mosapour Negari, Fariba (Iranian Journal of Archaeological Studies, 2024)
Keywords: Recension

New Materials on Ibāḍism in Iraq and Arabia at the Second and Third Centuries of Islam. Review of Al Salimi & Madelung, Ibāḍī Texts from the 2nd/8th Century (Leiden: Brill, 2018); Al Salimi, Ibadi Texts in Oman from the 3rd/9th Century (Leiden: Brill, 2021) - Baptiste, Enki (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2024)
Keywords: Recension

Recent Trends in the Studies of Ibadism in North Africa - Abdelfattah, Sami Samir (International Journal of Academic Research in Business and Social Sciences, 2024)
Keywords: Recension

Cheriau Raphaël, Intervention d’humanité. La Répression de la traite des esclaves à Zanzibar, années 1860-1900, Paris, CNRS Éditions, 2023, 400 p. ISBN 978-2-271-12720-4, 27 euros. - Frémeaux, Jacques (Outre-Mers, 2024)
Keywords: Recension

قراءة نقدية في كتاب الخطب المنبرية للشيخ إبراهيم بن محمد طلاى - بن دريسو, مصطفى بن محمد (‏الملتقى الدولي الشيخ إبراهيم طلاي وإسهاماته الحضارية, 2024)
Keywords: Recension

Cyrille Aillet, L’archipel Ibāḍīte. Une histoire des marges du Maghreb médiéval, Lyon, CIHAM Éditions, 2022 - Francesca, Ersilia (Der Islam, 2024)
Article Cyrille Aillet, L’archipel Ibāḍīte. Une histoire des marges du Maghreb médiéval, Lyon, CIHAM Éditions, 2022 (Mondes médiévaux). 592 p. ISBN: 978-2-9568426-4-4. was published on October 1, 2024 in the journal Der Islam (volume 101, issue 2).
Keywords: Recension

Virginie Prevost, Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe–XIIIe siècle), Monograph 10, London: Society for Libyan Studies, 2016, 232 pp., ISBN 978 1 900971 41 6. - Gutiérrez, González Carmen (Der Islam, 2024)
Keywords: Recension

PAUL M. LOVE Jr. The Ottoman Ibadis of Cairo: A History (Cambridge: Cambridge University Press, 2023). 236pp., $105.55 cloth. ISBN: 9781009254267. - Gaiser, Adam R. (Review of Middle East Studies, 2024)
Keywords: Recension

مستقبل سلطنة عمان بعد السلطان قابوس (مجلة كلية القانون والعلوم السياسية, 2024)
Keywords: Recension

مقاصد الشريعة عند الإمام نور الدين السالمي: قراءة في أطروحة د/ صالح عبد الرحمان - قشار, عمر بن بالحاج (2024)
Keywords: Recension

Ship Timbers from the Islamic Sites of al-Balid and Qalhat, Oman: Sewn-Plank Technology in the Indian Ocean during the 10–16th Centuries CE: Nautical Archaeology Society Monograph Ser. (NAS) 7, BAR International Series 3132, by Alessandro Ghidoni, Oxford, UK, BAR Publishing, 2023, 189pp., numerous illustrations, some colour, £58.00 (sbk), ISBN 9781407360577 - Zazzaro, Chiara (International Journal of Nautical Archaeology, 2024)
Keywords: Archéologie -- Oman; Recension

Ritter Stefan, Ben Tahar Sami (éd.), Studies on the Urban History of Meninx (Djerba). The Meninx Archaeological Project, 2015–2019 (Archäologische Forschungen, 43), Wiesbaden, DAI-Reichert, 2022, 1 vol. 21 × 30, Volume I, 454 p. + 11 pl., 248 fig. n/b et coul., ISBN : 978-3-75200-611-7. - Bejaoui, Fathi (Revue archéologique, 2024)
Keywords: Archéologie -- Djerba; Recension

Adam R. Gaiser, Sectarianism in Islam: The Umma Divided, Themes in Islamic History, xii, 237 pp., Cambridge: Cambridge University Press, 2023, ISBN 9781009325042. - Bernheimer, Teresa (Der Islam, 2024)
Keywords: Recension

L’archipel ibadite. Une histoire des marges du Maghreb médiéval, written by Cyrille Aillet - Love Jr, Paul M. (Arabica, 2024)
Keywords: Recension

Review of Local and Global Identities, (Studies on Ibadism and Oman 13) - Lohlker, Rüdiger (Wiener Zeitschrift für die Kunde des Morgenlandes, 2020)
Keywords: Recension

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’Ibadisme en Algérie (1882-1962) - Pace, Enzo (Archives de sciences sociales des religions, 2021)
Quel a été l’impact du colonialisme français sur ce que nous appelons sommairement l’islam ? Et en particulier sur les complexes relations que cette religion a nouées, au cours des années, avec les principales institutions sociales et politiques dans l’un des plus grands pays du Maghreb, l’Algérie ? Comment la domination coloniale a-t-elle été vécue et interprétée par les organes intellectuels du savoir et du pouvoir religieux musulman ? De manière passive, en subissant les effets inattendus ...
Keywords: Recension

Cultivating the past, living the modern: the politics of time in the Sultanate of Oman - Eldridge, Aaron F. (Politics, Religion & Ideology, 2024)
Keywords: Recension

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962), Paris, Éditions de la Sorbonne, « Bibliothèque historique des pays d’Islam », 2020, 398 p. - Perrier, Antoine (Le Mouvement Social, 2023)
Keywords: Recension

Abdulrahman Al-Salimi and Eric Staples, eds., Oman: A Maritime History. Studies on Ibadism and Oman , vol. 9, Hildesheim: Georg Olms Verlag, 2017. - Bahl, Christopher (Der Islam, 2023)
Keywords: Recension

Adam R. Gaiser: Sectarianism in Islam: The Umma Divided (Themes in Islamic History.) xii, 237 pp. Cambridge: Cambridge University Press, 2023. £70. ISBN 9781009325042. - Anchassi, Omar (Bulletin of the School of Oriental and African Studies, 2023)
Keywords: Recension

Zimmermann, Wolfgang et Gabriele Goldfuß, Magisches Musandam : Omans ferner Norden - Klinger, Thibaut (Arabian Humanities, 2023)
C’est un livre singulier que vient de publier au soir de sa carrière le géographe Wolfgang Zimmermann, associé à Gabriele Goldfuß, son épouse, universitaire spécialiste du bouddhisme, aux éditions allemandes Georg Olms, qui édite notamment la série d’ouvrages Studies on Ibadism and Oman. Le titre Magisches Musandam : Omans ferner Norden (Musandam magique : l’extrême Nord d’Oman) pourrait être celui d’un coffee-table book selon la terminologie anglo-saxonne : s’il présente près de 200 photogra...
Keywords: Recension

Fathi Ben Maammar, Tinfas seg Jerba - Ḥikāyāt amāzīghiyya jarbiyya - Brugnatelli, Vermondo (Journal of Amazigh Studies, 2023)
Keywords: Recension

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962). Paris, Éditions de la Sorbonne, 2020. 397 pp. €35.00 (pb). ISBN 979-10-351-0532-7. - Messaoudi, Alain (H-France Review, 2022)
Keywords: Recension

Adam R. GAISER, Shurāt Legends, Ibādī Identities. Martyrdom, Asceticism, and the Making of an Early Islamic Community, Columbia, South Carolina, University of South Carolina Press, 2016 - Francesca, Ersilia (Studi Magrebini, 2018)
Keywords: Recension

The Collective Biography of a Muslim Community - Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition By Paul M. Love Jr. Cambridge: Cambridge University Press, 2018. Pp. xxi + 206. 80.00, hardcover (ISBN: 9781108472500). - Hall, Bruce S. (The Journal of African History, 2021)
Keywords: Recension

Book Review: "Sultan Qaboos and Modern Oman, 1970-2020" by Allen James Fromherz and Abdulrahman al-Salimi, eds. - Junyent, Marc Martorell (Manara Magazine, 2022)
Keywords: Recension

Portugal in the Sea of Oman. Religion and Politics. Research on Documents, edited by Abdulrahman Al-Salimi and Michael Jansen and in collabaration with Pedro Pinto, Karsten Ley, and Helmut Siepmann - Biedermann, Zoltán (Journal of Early Modern History, 2021)
Keywords: Recension

الاقلية الذاتية للمنزابيين في الفترة الاستعنارية عزض ومناقشة: الجزء الأول - خواجة, عبد العزيز بن محمد (2022)
Keywords: Recension

Cyrille Aillet, L’archipel ibadite. Une histoire des marges du Maghreb médiéval - Prevost, Virginie (Bulletin critique des Annales islamologiques, 2023)
Voici enfin une monographie consacrée aux ibadites du Maghreb, depuis leur origine jusqu’au xve siècle, présentée en 2018 pour l’habilitation à diriger des recherches de Cyrille Aillet. Elle comprend onze chapitres, une chronologie, une vaste bibliographie et plusieurs index, notamment un très utile index des notions. Signalons, c’est assez peu courant, que l’index des personnes reprend aussi les noms des auteurs contemporains. Le livre retrace l’histoire des ibadites maghrébins et a pour obj...
Keywords: Recension

حول كتاب "الإمامة عند الإباضية" للشهيد بكير وعلي - قسوم, عبد الرزاق (الحياة, 2000)
Keywords: Recension

Qirāʾat min kitāb « Tārīkh Jarba wa ʿulamāʾihā ». Tahlīf al-Shaykh Sālim b. Yaʿqūb - Ibn Yaʿqūb, Nājī (al-Jazira, 2013)
Keywords: Recension

Book Review: “The Ibadi presence in Egypt” | مراجعة كتاب: الوجود الإباضي في مصر - Love Jr, Paul M. (Ibadi Studies | دراسات إباضية, 2020)
The cover of al-Wujūd al-Ibāḍī fī Miṣr (Maktabat Khazāʾin al-Āthār, 2018). I borrow the image here from a remarkably detailed summary of the book available in Arabic here. I recently had the pleasu…
Keywords: Recension

Vient de paraître: Djerba, l’île enchantée … - Hamza, Alya (La Presse de Tunisie, 2020)
« Djerba, l’île enchantée »  répond, certes, aux critères de « Beau Livre », de par l’élégance de sa présentation, la beauté de ses photos, le soin de sa
Keywords: Recension

Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1962), written by Augustin Jomier - Francesca, Ersilia (Studia Islamica, 2022)
Keywords: Recension

Il Kharigismo come concetto politico nel mondo contemporaneo. Riflessioni sullo scontro ideologico tra Al-Azhar e Sayyid Quṭb - Cascio, Roberto (Occhialì, 2018)
Keywords: Recension

Cyrille Aillet, L’ibadisme dans les sociétés de l’Islam médiéval. Modèles et interactions - Rebstock, Ulrich (Die Welt des Islams, 2022)
Keywords: Recension

Uṣūl al-Dīn (The Fundamentals of the Faith). By Tibghūrīn b. īsā al-Malshūṭī. Edited by 'Amr Khalifa Ennami and translated into English by Trevor Le Gassick - Gaiser, Adam R. (Journal of the American Oriental Society, 2022)
Keywords: Foi -- Traité -- 12e siècle; Malshūṭī, Tibghūrīn b. ʿĪsā al-; Recension

Hannah-Lena Hagemann: The Khārijites in Early Islamic Historical Tradition: Heroes and Villains. (Edinburgh Studies in Classical Islamic History and Culture.) xii, 328 pp. Edinburgh: Edinburgh University Press, 2021. £85. ISBN 978 1 4744 5088 1. - Kenney, Jeffrey T. (Bulletin of the School of Oriental and African Studies, 2022)
Keywords: Recension

Islam, réforme et colonisation: Une histoire de l’ibadisme en Algérie (1882–1962) - Chih, Rachida (The Journal of North African Studies, 2022)
Keywords: Recension

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition By Paul M. Love Jr - Ghazal, Amal N. (Journal of Islamic Studies, 2021)
Typically, siyar in the Islamic tradition are biographical texts outlining the life and times of individuals, whether scholars or otherwise. Siyar are not known to offer coherent historical narratives, nor are they complete historical chronicles. They are usually compiled in an incremental manner, passing from one generation to another, creating a chain of individuals and/or communities across time and space. Despite their prominence, they have mostly served the historical profession, more or less, as biographical dictionaries. Ibadi siyar in North Africa belong to this same genre and have served a similar purpose. Paul Love’s book uses an innovative methodology in his analysis of siyar that changes the way historians can use and read these texts.
Keywords: Recension

Islam, réforme et colonisation: une histoire de l'ibadisme en Algérie, 1882–1962 by Augustin Jomier - Brower, Benjamin Claude (Arab Studies Journal, 2022)
Keywords: Recension

Al-Salimi, Abdulrahman: On the Reception of Early Ibadi Theology. A Commentary on the Book on Monotheism by ‘Abd Allāh b. Yazīd al-Fazārī (2nd/8th Century). - Metzler, Berenike (Orientalistische Literaturzeitung, 2022)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

Review: The Essentials of Ibāḍī Islam - Woodlock, Rachel (American Journal of Islam and Society, 2014)
When writing about Islamic sectarian diversity, the vast majority of authorspay attention only to Sunni and Shi‘i Islam. Yet there exists a third groupdrawn from the earliest conflicts that rent the Muslim ummah apart: the Ibadis.If they are mentioned at all, it is usually little more than a footnote remarkingthat this group is the remnant of the Khariji secession in 657. Yet this thirdgroup – today predominant in Oman and Zanzibar, with populations also inAlgeria, Libya, and Tunisia – played an important political and theologicalrole in the immediate post-Prophetic period. Due to this word’s negative connotation,however, Ibadis do not refer to themselves as Kharijis, a group historicallyviewed as religious extremists by other Muslims. Instead, “Ibadi”comes from the enigmatic Abdullah ibn Ibad/Abad who died early in theeighth century, although, as the author notes, it is likely that his successor Jabiribn Zayd played a more important role in founding the group.Addressing the dearth of English-language resources on Ibadi beliefs, ValerieJ. Hoffman has written The Essentials of Ibāḍī Islam in “an attempt tointroduce Ibadi Islamic theology to students and scholars of Islam” (p. 4) – atask in which she succeeds admirably. Her book is primarily a translation ofa theological primer and supplementary text, preceded by a short introductionon the origins and history of Ibadi Islam to orient the readers and prepare them ...
Keywords: Recension

Ismail Albayrak, Approaches to Ibāḍī Exegetical Tradition - Baptiste, Enki (Bulletin critique des Annales islamologiques, 2022)
Ismail Albayrak is Professor at the Australian Catholic University in Melbourne. He has been studying Islamic theology and exegesis for two decades. This present book deals with the little-known field of Ibadi studies. Scholars are increasingly beginning to appreciate Ibadi materials as these sources offer new perspectives to understand the formative period of Islam. The texts produced by the communities either in North Africa or in Arabian Peninsula are better known and most of them are now ...
Keywords: Recension

Paul Love, Ibadi Muslims of North Africa. Manuscripts, Mobilization, and the Making of a Written Tradition - Baptiste, Enki (Bulletin critique des Annales islamologiques, 2021)
Paul Love, actuellement Assistant Professor à l’Université d’Al Akhawayn (Ifrane, Maroc), est un spécialiste de l’histoire de l’ibāḍisme médiéval au Maghreb. Dans cet ouvrage, il livre le fruit de ses recherches de doctorat. L’ibāḍisme ne cesse d’attirer de nouveaux chercheurs et les récentes publications sur l’histoire de ces groupes religieux disséminés dans les marges de l’Empire islamique témoignent de la richesse du corpus de sources à explorer. Les sources ibāḍites maghrébines, que l’on...
Keywords: Recension

Cyrille Aillet (éd.), L’ibadisme dans les sociétés de l’Islam médiéval. Modèles et interactions - Baptiste, Enki (Bulletin critique des Annales islamologiques, 2020)
L’ibāḍisme reste le parent pauvre des études d’islamologie et d’histoire des mondes musulmans médiévaux. Cet ouvrage est néanmoins une contribution supplémentaire à l’important chantier de renouvellement des études portant sur les sociétés ibāḍites maghrébines et orientales prémodernes. Désormais mieux connue grâce aux travaux pionniers de J. Wilkinson, de P. Crone et, plus récemment, de C. Aillet et d’A. Gaiser, cette école juridique, parfois considérée comme la troisième branche de l’islam,...
Keywords: Recension

Rose Jeffrey I., Hilbert Yamandu H., Marks Anthony E., Usik Vitaly I. 2019. The first peoples of Oman. Palaeolithic archaeology of the Nejd plateau - Groucutt, Huw S. (Paléorient, 2020)
The Dhofar region in the southwest of Oman is a peculiar, and special, corner of Arabia. It represents the eastern-most extent of the highland spine of Arabia which extends down the west coast and then swings eastwards through Yemen. Traditionally Dhofar had more to do with areas to its west than to the rest of Oman, with social and linguistic connections to areas in modern-day Yemen. Likewise, Dhofar is a primarily Sunni Muslim area in contrast to the Ibadism dominant in the north of Oman. T...
Keywords: Recension

Review of Zanzibar: A Plan for the Historic Stone Town; Doors of Zanzibar - Frankl, P.J.L. (British Journal of Middle Eastern Studies, 2000)
Keywords: Recension

Review of The Emergence of States in a Tribal Society: Oman under Sa‛id bin Taymur, 1932-1970 - Ochsenwald, William (The American Historical Review, 2008)
Keywords: Recension

Prevost Virginie, L’aventure ibâḍite dans le sud tunisien. Effervescence d’une région méconnue (viiie-xiiie siècle), Helsinki, Academia Scientiarum Fennica, 2008, 480 p. - Amara, Allaoua (مجلة الآداب والعلوم الإنسانية, 2011)
Keywords: Recension

Review of Historical Muscat. An illustrated guide and gazetteer. (Handbook of Oriental Studies, section one, The Near and Middle East, Vol. 88) - Scholz, Fred (Wiener Zeitschrift für die Kunde des Morgenlandes, 2011)
Keywords: Recension

Review of In the Shadow of the Ancestors: The Prehistoric Foundations of the Early Arabian Civilization in Oman - Magee, Peter (American Journal of Archaeology, 2008)
Keywords: Recension

In the Time of Oil: Piety, Memory & Social Life in an Omani Town. Mandana E. Limbert. Stanford, CA: Stanford University Press, 2010 - Gilbert, Paul (Anthropology of Work Review, 2012)
Keywords: Recension

“Switzerland of Arabia”: Omani Foreign Policy and Mediation Efforts in the Middle East - Worrall, James (The International Spectator, 2021)
In recent years, Oman has been recognised as a key mediator in the Gulf and the wider Middle East. The successful completion of the 2015 Iran nuclear deal, in particular, firmly cemented its reputation as a peacemaker. To fully understand Omani mediation practices in the region, Muscat’s mediation must be placed within the context of the Sultanate’s wider foreign policy, and all known mediations must be assembled in one place in order to develop a typology to better understand forms and patterns. Ultimately, mediation both serves and is enabled by the Sultanate’s foreign policy. This was not an inevitable outcome. Over the course of Qaboos’ reign, Oman has developed into an ‘Interlocutor State’, in which the practice of mediation has become an important tool in furthering the central goals of preserving Oman’s independent foreign policy, and thus ultimately the Sultanate’s sovereignty and security itself.
Keywords: Recension

Review of The Mehri Language of Oman - Morris, Miranda (Journal of the American Oriental Society, 2012)
Keywords: Recension

Prevost Virginie, L’aventure ibâḍite dans le sud tunisien. Effervescence d’une région méconnue (viiie-xiiie siècle), Helsinki, Academia Scientiarum Fennica, 2008, 480 p. - Nigst, Lorenz (Revue des mondes musulmans et de la Méditerranée, 2010)
Whoever followed Virginie Prevost’s work over the past years, is well aware of the fact that she established herself as an important scholar on the history of the Ibâḍīs. The volume at hand is entitled « L’aventure ibâḍite dans le sud tunisien. Effervescence d’une région méconnue ». It is an impressive testimony to her ongoing work in that field and a momentous presentation of the results her painstaking research has yielded so far. The volume is impressive both in the wealth of sources it sc...
Keywords: Recension

Review of In the Shadow of the Ancestors. The Prehistoric Foundations of the Early Arabian Civilization in Oman - Lombard, Pierre (Paléorient, 2009)
Keywords: Recension

Review of The Epistle of Sālim Ibn Dhawān - Gilliot, Claude (Studia Islamica, 2003)
Keywords: Recension

Review of Historical Mosques and Shrines of Oman (BAR International Series, 938) - Comneno, Maria Adelaide Lala (Quaderni di Studi Arabi, 2002)
Keywords: Recension

Review of Oman: Political Development in a Changing World - Deeb, Mary-Jane (The American Political Science Review, 2001)
Keywords: Recension

Review of Oman under Qaboos: From Coup to Constitution, 1970-1996, W. Lynn Rigsbee, II - Peterson, John E. (Middle East Journal, 2001)
Keywords: Recension

Oman Under Qaboos: From Coup to Constitution, 1970-1996; Calvin Allen, Jr.; W. Lynn Rigsbee II - Farah, Caesar E. (Digest of Middle East Studies, 2000)
Keywords: Recension

Meouak Mohamed (éd.): Biografías magrebíes. Identidades y grupos religiosos, sociales y políticos en el Magreb medieval. - Buresi, Pascal (Bulletin critique des Annales islamologiques, 2013)
Keywords: Recension

Marc Lavergne, Brigitte Dumortier : L’Oman contemporain. État, territoire, identité - Bondue, Jean-Pierre (Espace populations sociétés. Space populations societies, 2004)
Keywords: Recension

Lavergne M. et Dumortier B. (dir.), L'Oman contemporain. État, territoire, identité - Troin, Jean-François (Annales de géographie, 2003)
Keywords: Recension

Review of In the Wake of the Dhow: The Arabian Gulf and Oman - Ray, Himanshu Prabha (Journal of the Economic and Social History of the Orient, 2003)
Keywords: Recension

Jeffrey T. Kenney, Muslim Rebels: Kharijites and the Politics of Extremism in Egypt (Oxford: Oxford University Press, 2006). Pp. 234. $45.00 cloth. - Kalmbach, Hilary (International Journal of Middle East Studies, 2009)
Keywords: Recension

Review of Oman: The Islamic Democratic Tradition - Solomon, Gina; Latorre, Aida (Middle East Studies Association Bulletin, 2007)
Keywords: Recension

Latifah al-Bakkay, Harakat al-Khawarij. Nash'atuha wa-tatawwuruha ila nihayat al-'ahd al-umawi (37-132 H.) - Melchert, Christopher (Al-ʿuṣūr al-wusṭa, The Bulletin of Middle East Medievalists, 2002)
Keywords: Recension

Heureux qui, comme Kindynis,... - Harbaoui, Chaâbane (2010)
Keywords: Recension

Review of The Emergence of States in a Tribal Society: Oman under Sa'id bin Taymur, 1932-1970 - Allen, Jr, Calvin H. (Middle East Journal, 2007)
Keywords: Recension

Review of Oman: The Islamic Democratic Tradition - Allen, Jr, Calvin H. (International Journal of Middle East Studies, 2008)
Keywords: Recension

Review of Oman Emerges: An American Company in an Ancient Kingdom - Allen, Jr, Calvin H. (Middle East Journal, 2011)
Keywords: Recension

Review of Oman's Insurgencies: The Sultanate's Struggle for Supremacy; Oman: Politics and Society in the Qaboos State - Allen, Jr, Calvin H. (Middle East Journal, 2010)
Keywords: Recension

Review of In the Wake of the Dhow: The Arabian Gulf and Oman - Allen, Jr, Calvin H. (International Journal of Middle East Studies, 2004)
Keywords: Recension

Bernardie-Tahir, Nathalie (dir.) (2008) L’autre Zanzibar. Géographie d’une contre-insularité. Paris, Karthala, 379 p. (ISBN 978-2-84586-946-2) - Bouchard, Christian (Cahiers de géographie du Québec, 2009)
Un article de la revue Cahiers de géographie du Québec, diffusée par la plateforme Érudit.
Keywords: Recension

Oman: Politics and Society in the Qaboos State - By Marc Valeri: Oman . . . - Wimpy, Cameron (Digest of Middle East Studies, 2010)
Keywords: Recension

Review of Il sultanato di Zanzibar nel XIX secolo: traffici commerciali e relazioni internazionali; Makran, Oman and Zanzibar. Three-Terminal Cultural Corridor in the Western Indian Ocean (1799-1856), Beatrice Nicolini - Bernardi, Bernardo (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 2006)
Keywords: Recension

Review of Changing Rural Systems in Oman. The Khabura Project - Pater, Ben de (GeoJournal, 2000)
Keywords: Recension

Review of Makran, Oman and Zanzibar. Three-Terminal Cultural Corridor in the Western Indian Ocean (1799-1856) - Loimeier, Roman (Die Welt des Islams, 2006)
Keywords: Recension

Valerie Hoffman, The Essentials of Ibāḍī Islam - Thompson, Alexs (The Journal of Religion, 2015)
Keywords: Recension

Review of Mehri Texts from Oman (Based on Field Materials of T. M. Johnstone) - Kaye, Alan S. (Journal of the American Oriental Society, 2001)
Keywords: Recension

Review of In the Wake of the Dhow - Kaye, Alan S. (Bulletin of the School of Oriental and African Studies, 2003)
Keywords: Recension

Dhows and the Colonial Economy of Zanzibar, 1860-1970 - Sheriff, Abdul Mohamed Hussein (Economic History Association, 2005)
Keywords: Recension

Laris Kindynis, Djerba, l'île enchantée de mon enfance - Merimi, Mohamed (Rawafid, 2010)
Keywords: Recension

Review : Makran, Oman and Zanzibar: Three-Terminal Culural Corridor in the Western Indian Ocean, 1799-1856, Beatrice Nicolini, Leiden: E. J. Brill, 2004. ISBN 9004137807, xxvii + 179 pp., index, four illustrations - Limbert, Mandana E. (Iranian Studies, 2006)
Keywords: Recension

GAISER Adam R , Shurāt Legends, Ibāḍī Identities. Martyrdom, Asceticism, and the Making of an Early Islamic Community, Columbia, University of South Carolina, 2016, 223 p. - Aillet, Cyrille (Revue des mondes musulmans et de la Méditerranée, 2019)
Keywords: Recension

Early Ibāḍī Theology : Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī, written by Abdulrahman al-Salimi and Wilferd Madelung - Aillet, Cyrille (Arabica, 2017)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

أثر تحقيق رسالة بن ذكوان في تطور الدراسات حول الأباضية - قطاط, فريد (الحياة الثقافية, 2004)
Keywords: Recension

Abrous Dahbia, La Société des Missionnaires d’Afrique à l’épreuve du mythe berbère. Kabylie, Aurès, Mzab, Préface de Salem Chaker, Paris/Louvain, Éditions Peeters, 2007, 151 p. - Claudot-Hawad, Hélène (Revue des mondes musulmans et de la Méditerranée, 2010)
Les membres de la Société des Missionnaires d’Afrique sont davantage connus sous le nom de « Pères Blancs » et de « Sœurs Blanches ». Cette congrégation catholique fut très active dans le nord de l’Afrique, en Tunisie et surtout en Algérie, à la fin du xixe siècle. À partir d’un minutieux travail sur les fonds d’archives de la Société, Dahbia Abrous interroge deux aspects principaux de la présence et de l’action missionnaires : d’une part, l’entreprise prosélyte, ses principes et ses stratégi...
Keywords: Recension

Sur les traces des Juifs sahariens - Warscheid, Ismail (La Vie des idées, 2015)
À propos de : Sarah A. Stein, Saharan Jews and the Fate of French Algeria, Chicago
Keywords: Judaïsme -- Mzab; Recension

Review of Ibadi Theology: Rereading Sources and Scholarly Works - Adem, Rodrigo (Journal of the American Oriental Society, 2018)
Keywords: Recension

Review : Makran, Oman, and Zanzibar: Three-Terminal Cultural Corridor in the Western Indian Ocean (1799-1856), trans. Penelope-Jane Watson, Islam in Africa Series, vol. 3 (Leiden: Brill, 2004). Pp. 191. $112.00 cloth. - Risso, Patricia (International Journal of Middle East Studies, 2005)
Keywords: Recension

Adam R. Gaiser. Muslims, Scholars, Soldiers: Origin and Elaboration of the Ibādī Imāmate Traditions. New York: Oxford University Press, 2010. viii + 203 pp. $80.00 (cloth), ISBN 978-0-19-973893-9. - Love Jr, Paul M. (H-Net Reviews, 2014)
Keywords: Recension

Mounia Chekhab-Abudaya . Le qṣar, type d'implantation humaine au Sahara: architecture du Sud Algérien (Cambridge Monographs in African Archaeology 91). 2016. xiv+340 pages; numerous colour and b&w illustrations. Oxford: Archaeopress 978-1-78491-347-2 paperback £50. - Fentress, Elizabeth (Antiquity, 2017)
Keywords: Recension

Une enfance dans M'Zâb de Abderrahmane Zakad. Éditions Alpha, Alger, 2008, 226 pages. (L'Expressiondz, 2008)
Keywords: Recension

Review : Muhammad al-Mahruqi (ed.), Mugamir 'umani fi adgal Ifriqya. Hayat Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1905), al-ma'riif bi-TibuTib [Un aventurier Omanais au coeur de l'Afrique. La vie de Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1900), connu sous le nom de Tippo Tip], Cologne, Al-Kamel, 2006 (210 p.). - Luffin, Xavier (Annales Aequatoria, 2008)
Keywords: Recension; Tippo Tip (1837-1905)

Review : Oman under Qaboos. From Coup to Constitution, 1970-1996 - Hertog, Stephen (British Journal of Middle Eastern Studies, 2007)
Keywords: Recension

Review: Traditional Arts in Southern Arabia: Music and Society in Sohar, Sultanate of Oman - Hassan, Scheherazade Qassim (Yearbook for Traditional Music, 2010)
Keywords: Recension

Review: A Maritime Lexicon Arabic Nautical Terminology in the Indian Ocean - Acevedo, Juan (Rutter Book Review, 2020)
Keywords: Recension

Cuperly Pierre, Toute Langue dit Dieu. Textes réunis et édités par Yacine Daddi Addoun and Soufien Mestaoui, Ibadica Geuthner, Paris 2020, Culture et Société, 303 pp. + 39 pp. in Arabic; Théologie ibâḍite, 226 pp. + 75 pp. in Arabic. - Fitzgerald, Michael L. (Islamochristiana, 2020)
Keywords: Recension

Review: [Muslim Rebels: Kharijites and the Politics of Extremism in Egypt, by Jeffrey T. Kenney. New York: Oxford University Press, 2006. xi + 184 pages. Notes to p. 205. Bibl. to p. 216. Indexto p. 221. $45.] - Jankowski, James (Middle East Journal, 2007)
Keywords: Recension

Review: An Arabian Utopia: The Western Discovery of Oman, by Alistair Hamilton London: Oxford University Press, 2010 - Peterson, John E. (Middle East Journal, 2011)
Keywords: Recension

Review: Mehri Texts from Oman: Based on the Field Materials of T. M. Johnstone, by Harry Stroomer. (Semitica Viva, Bd. 22) 303 pages, map, bibliography, footnotes, transcription table. Wiesbaden, Germany: Harrassowitz Verlag, 1999. DM168.00 (Paper) isbn 3-447-04215-X - Cross, Carmen (Middle East Studies Association Bulletin, 2001)
Keywords: Recension

Review: Proconsul to the Middle East: Sir Percy Cox and the End of Empire - By John Townsend: Proconsul to the Middle East - Frantzman, Seth J. (Digest of Middle East Studies, 2011)
Keywords: Recension

Review : Hoffmann-Ruf, Michaela: Scheich Muhsin bin Zahrän al-'Abri. Tribale Macht im Oman des 19. Jahrhunderts. Berlin (Klaus Schwarz) 2008. 46 Euro. ISBN 978-3-97997-353-8. - Lohlker, Rüdiger (Wiener Zeitschrift für die Kunde des Morgenlandes, 2009)
Keywords: Recension

Review: Seafaring in the Arabian Gulf and Oman: The People of the Dhow, by DIONISIUS A. AGIUS. London: Kegan Paul, 2005.285 pages, illustrations,glossary,name index. UK<£95.00 (Cloth) ISBN 0-7103-0939-2 - Nicolini, Beatrice (Middle East Studies Association Bulletin, 2006)
Keywords: Recension

Mulāḥaẓāt ḥawla Kitāb “al-Lawwāḥ al-Kharūṣī” - Būḥajjām, Muḥammad b. Qāsim Nāṣir (2004)
Keywords: Recension

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Ibrahim (International Journal of Middle East Studies, 2000)
Keywords: Recension

Review : Cook, Michael: (2000) Commanding right and forbidding wrong in Islamic thought. Cambridge: Cambridge University Press, 2000, (xvii, 702 pp.; 23x15 cm.). ISBN 0521661749. - Sajjad, Rizvi (Transcendent Philosophy, 2001)
Keywords: Recension

PREVOST, Virginie. Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe-XIIIe siècle). London: Society for Libyan Studies Monograph 10, 2016, 231 páginas - Meouak, Mohamed (Miscelánea de estudios árabes y hebraicos, 2020)
Keywords: Recension

Review : Traditional Arts in Southern Arabia: Music and Society in Sohar, Sultanate of Oman - Urkevich, Lisa (The World of Music, 2009)
Keywords: Recension

BAKELLI, Ahmed. De l’histoire des ibadites au Maghreb. Regard libre sur les chroniques d’Abu Zakaria. Alger : Casbah Éditions, 2009, 379 pages. - Prevost, Virginie (Al-Andalus Magreb, 2014)
Keywords: Recension

Review of John C. Wilkinson. Ibadism: origins and early development in Oman - Gaiser, Adam R. (Jerusalem Studies in Arabic and Islam, 2012)
Keywords: Recension

Muḥammad ḤASAN, al-Ğuġrāfiya l-tāriḫiyya li-Ifrīqiya min al-qarn al-awwal ilā al-qarn al-tāsi‘ (VII-XV): fusūl fī tārīḫ al-mawāqi‘ wa-l-masālik wa-l- mağālāt, Beyrouth, Dār al-kītāb al-ğadīd, 2004, 312 p., ISBN: 9959-29- 144-8. - Amara, Allaoua (Arabica, 2010)
Keywords: Recension

BENKARI-BOUDIDAH, Naïma, L’architecture des mosquées Ibadites au M’Zab, Djerba et Oman. Lecture des principes de conception et de construction, Saarbrücken, Presses Académiques Francophones, 2013-2014, 2 tomes, 682 et 485 pp. - Prevost, Virginie (Al-Qantara : Revista de Estudios Arabes, 2016)
Keywords: Recension

Ibāḍī Texts from the 2nd/8th Century - Love Jr, Paul M. (Al-Masāq, 2019)
Keywords: Recension

Review : Bendrissou Salah, Implantation des Mozabites dans l’Algérois entre les deux-guerres - Ben Madani, Mohamed (The Maghreb Review, 2003)
Keywords: Recension

Ibadi Texts for the 2nd/8th Century - Rizvi, Sajjad (The Muslim World Book Review, 2020)
A quarterly publication of the Islamic Foundation, Markfield, Leicestershire, UK. This journal aims to present the Muslim viewpoint on books and issues which concern Islam and Muslims.
Keywords: Recension

Ersilia Francesca. Teoria e pratica del commercio nell’Islam medievale. I contratti di vendita e di commenda nel diritto ibadita - Aguirre Sádaba, F. J. (Jerusalem Studies in Arabic and Islam, 2004)
Keywords: Recension

al-Kharusi, Kahlan: Āthār al-Rabī‘ b. Ḥabīb. Edition and Study. Wiesbaden: Harrassowitz 2016. X, 172 S. 8° = Abhandlungen für die Kunde des Morgenlandes 106. Brosch. € 48,00. ISBN 978-3-447-10634-4. - Grobbel, Gerald (Orientalistische Literaturzeitung, 2019)
Keywords: Recension

Valerie J. Hoffman, The Essentials of Ibāḍī Islam, Syracuse, Syracuse University Press, 2012, xii+344 p., ISBN : 978-0-8156-3288-7, 32,47 € (relié). - Prevost, Virginie (Arabica, 2013)
Keywords: Recension

Review of Early Ibāḍī Literature. Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb. Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra. (Abhandlungen für die Kunde des Morgenlandes, 75) - Prevost, Virginie (Wiener Zeitschrift für die Kunde des Morgenlandes, 2012)
Keywords: Recension

L’aventure ibadite dans le Sud tunisien: Effervescence d’une région méconnue - Aillet, Cyrille (Al-Masāq, 2012)
Keywords: Recension

Shurāt Legends, Ibāḍī Identities: Martyrdom, Asceticism, and the Making of an Early Islamic Community, written by Adam R. Gaiser, 2016 - Sahner, Christian C. (Islamic Law and Society, 2020)
"Shurāt Legends, Ibāḍī Identities: Martyrdom, Asceticism, and the Making of an Early Islamic Community, written by Adam R. Gaiser, 2016" published on 06 Aug 2020 by Brill.
Keywords: Recension

Les mosquées ibadites du djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe-XIIIe siècle), written by Virginie Prevost, 2016 - Rebstock, Ulrich (Die Welt des Islams, 2019)
Keywords: Recension

Al-Salimi, Abdulrahman / Madelung, Wilferd: Early Ibāḍī Literature. 2011. - Rebstock, Ulrich (Orientalistische Literaturzeitung, 2017)
Keywords: Recension

The Emergence of States in a Tribal Society: Oman under Sa'id bin Taymur, 1932-1970by Uzi Rabi - Kechichian, Joseph Albert (The International History Review, 2007)
Keywords: Recension

Uzi Rabi. The Emergence of States in a Tribal Society: Oman under Sa‘id bin Taymur, 1932–1970 .:The Emergence of States in a Tribal Society: Oman under Sa ʕ id bin Taymur, 1932–1970 - Ochsenwald, William (The American Historical Review, 2008)
Keywords: Recension

Uzi Rabi The Emergence of States in a Tribal Society: Oman under Saʿid bin Taymur, 1932–1970 (Portland, Ore.: Sussex Academic Press, 2006). Pp. 320. $67.50 cloth. - Riphenburg, Carol J. (International Journal of Middle East Studies, 2008)
Keywords: Recension

Oman under Qabus: From Coup to Constitution, 1970-1996 by Calvin Allen, Jr.; W. Lynn Rigsbee, II - Rabi, Uzi (Middle Eastern Studies, 2001)
Keywords: Recension; Vie politique -- Oman -- 1970-2020

The Emergence of States in a Tribal Society: Oman Under Sa'id bin Taymur, 1932-1970 : Uzi Rabi - Silverberg, Sanford R. (Digest of Middle East Studies, 2008)
Keywords: Recension

Miklos Muranyi: The First Compendium of Ibadi Law: The Mudawwana by Abu Ghanim Bishr b. Ghanim al-Khurasani. (Studies on Ibadism and Oman.) 159 pp. Hildesheim: Georg Olms Verlag, 2018. €38. ISBN 978 3 487 15678 1. - Propst, Amanda (Bulletin of the School of Oriental and African Studies, 2019)
Keywords: Fiqh -- Libye -- 8e siècle; Recension

The Epistle of Sālim ibn Dhakwān, by Patricia Crone and Fritz Zimmermann. New York: Oxford University Press, 2001. 407 pages, appendices, bibliography. US $90.00 (cloth) ISBN 0-19-815265-5 - Jarrar, Maher (Middle East Studies Association Bulletin, 2003)
Keywords: Recension

P. Crone and F. W. Zimmermann: The Epistle of Salim Ibn Dhakwan. (oxford Oriental Monographs.) Xi, 407 Pp. Oxford: Oxford University Press, 2001. £65. - Melchert, Christopher (Bulletin of the School of Oriental and African Studies, 2002)
Keywords: Recension

Abdel-Hakim Ourghi, Die Reformbewegung in der neuzeitlichen Ibāḍīya. Leben und Wirken von Muḥammad b. Yūsuf Aṭfaiyaš 1236–1332 h.q. (1821–1914), Würzburg: Ergon-Verlag 2008. 399 S., ISBN 978-3-89913-660-9. Preis: € 52.– - Schmidinger, Thomas (Der Islam, 2012)
Keywords: Recension

Abdulrahman Al-Salimi and Wilferd Madelung (eds): Ibāḍī Texts from the 2nd/8th Century. (Islamic History and Civilization. Studies and Texts 133.) vi, 392 pp. Leiden: Brill. 2018. €110. ISBN 978 90 04 33064 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2018)
Keywords: Recension

Early Islamic Law in Basra in the 2nd/8th Century. Aqwāl Qatāda b. Diʿāma al-Sadūsī, written by Abdulrahman al-Salimi - Benkheira, Mohammed Hocine (Studia Islamica, 2020)
Keywords: Recension

آراء و دراسات حول كتاب عمان الديمقراطية الإسلامية للدكتور حسين غباش - الخليلي, أحمد بن حمد (دار الفارابي, 2010)
Keywords: Recension

مائة كتاب أباضي - إمام, محمد كمال الدين (وزارة الأوقاف والشؤون الدينية, 2013)
Keywords: Recension

أبناء جزيرة جربة في الحركة الوطنية 1881-1961 - الصغير, عميرة علية (مجلة روافد, 2008)
Keywords: Recension

Clients Reviews on the Web: Toward a New Knowledge of Touristic Space. Case of Djerba in Tunisia - Neifar, Bassem (Communication, technologie et développement, 2016)
Keywords: Recension; Tourisme -- Djerba

سلسلة الدراسات الإباضية والعمانية المجلد الثاني: كتاب عمان وما وراء البحار - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

الإباضية في منطقة المحيط الهندي.. القسم الأول - شرق أفريقيا - بنت ناصر, فاطمة (شباب التفاهم, 2018)
Keywords: Recension

Review of The Ports of Oman - Hoffmann-Ruf, Michaela (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Review of Today's Perspectives on Ibadi History - Jomier, Augustin (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Rabah NABLI, Les Entrepreneurs tunisiens. La difficile émergence d’un nouvel acteur - Ferréol, Gilles (Revue européenne des migrations internationales, 2009)
Keywords: Recension

Review of L'aventure ibāḍite dans le Sud tunisien. Effervescence d'une région méconnue - Szombathy, Zoltán (Acta Orientalia Academiae Scientiarum Hungaricae, 2011)
Keywords: Recension

Review of Early Ibāḍī Theology. Six kalām texts by ʿAbd Allāh b. Yazīd al-Fazārī. (Islamic History and Civilization 106) - Thiele, Jan (Wiener Zeitschrift für die Kunde des Morgenlandes, 2016)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

Cyrille Aillet, Patrice Cressier, Sophie Gilotte (éd.), Sedrata. Histoire et archéologie d’un carrefour du Sahara médiéval à la lumière des archives inédites de Marguerite van Berchem: Madrid, Casa de Velázquez (« Collection de la Casa de Velázquez », 161), 2017, 497 p. - Mesnil, Emmanuelle Tixier du (Médiévales, 2020)
Keywords: Archéologie -- Sedrata; Recension

Stuart Laing. Tippu Tip: Ivory, Slavery and Discovery in the Scramble for Africa - Kyle, Michael (Asian Affairs, 2018)
Keywords: Esclavage -- Zanzibar; Recension; Tippo Tip (1837-1905)

The Life of Tippu Tip. Tippu Tip: Ivory, Slavery, and Discovery in the Scramble for Africa - Mathews, Nathaniel (The Journal of African History, 2019)
Keywords: Esclavage -- Zanzibar; Recension; Tippo Tip (1837-1905)

Augustin Jomier, Islam, réforme et colonisation. Une histoire de l’ibadisme en Algérie (1882-1931) - Richaud, Jean-David (Lectures, 2020)
Keywords: Recension

Virginie PRÉVOST, L’aventure ibāḍite dans le Sud tunisien. Effervescence d’une région méconnue, Helsinki, Academia Scientiarum Fennica, 2008, 479 p. - Amara, Allaoua (Studia Islamica, 2013)
Keywords: Recension

L’aventure ibāḍite dans le Sud tunisien (VIIIe-XIIIe siècle). Effervescence d’une région méconnue - Garnier, Sébastien (Arabica, 2014)
Keywords: Recension

Le M’Zab : études d’anthropologie historique et culturelle, written by Brahim Cherifi - Prevost, Virginie (Arabica, 2016)
Keywords: Recension

Al-Ibāḍiyya, a Bibliography : Second, revised and enlarged edition, written by Martin Custers - Prevost, Virginie (Arabica, 2016)
Keywords: Recension

The Arabs and the Scramble for Africa by John C. Wilkinson, and: The Ottoman Scramble for Africa: Empire and Diplomacy in the Sahara and the Hijaz by Mostafa Minawi, and: Identifying With Nationality: Europeans, Ottomans, and Egyptians in Alexandria by Will Hanley - Mathews, Nathaniel (Journal of World History, 2019)
Keywords: Recension

ARABS AND THE SCRAMBLE FOR AFRICA - The Arabs and the Scramble for Africa. By John C. Wilkinson. Sheffield, England: Equinox Publishing, 2015. Pp. xiv + 497. £70.00/$115.00, hardback (ISBN 9781781790687). - Nicolini, Beatrice (The Journal of African History, 2018)
Keywords: Recension

Oman: A Thousand Years of Democratic Tradition * by Hussain Ghubash - Jones, Jeremy (Journal of Islamic Studies, 2007)
Keywords: Recension

Islamic Reform and Arab Nationalism. Expanding the Crescent from the Mediterranean to the Indian Ocean (1880s-1930s) - Bang, Anne K. (Journal of Islamic Studies, 2013)
Keywords: Recension

Muslims, Scholars, Soldiers: The Origin and Elaboration of the Ibadi Imamate Traditions * By ADAM GAISER. - Salimi, Abdulrahman al- (Journal of Islamic Studies, 2013)
Keywords: Recension

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition, by Paul M. Love - Prevost, Virginie (The English Historical Review, 2020)
This interesting and concise book finds its origin in Paul Love’s doctoral thesis defended in 2016 at the University of Michigan. It presents an innovative study of medieval Ibadi North-African Siyar. In the Maghrib, Siyar are books containing anecdotal and biographical information about individuals, playing the role of chronicle-style history; they function as prosopographies, collective biographies in which stories about individual members come together to form the biography of the community, constructing a North-African Ibadi tradition (p. xx). Love’s book tells the story of the compilation, adaptation and circulation of that prosopographical corpus through five scholars’ works. The pioneer is Abû Zakariyyâ’ al-Wârjalânî who provided Ibadi scholars of the second part of the eleventh century with a cohesive narrative of their history, when the community was suffering an ongoing numerical decline; he chose to write in the Arabic language at a time when use of the Berber language was also in decline. The author then studies the works of al-Wisyânî, al-Darjînî and al-Barrâdî. The last Ibadi scholar is al-Shammâkhî (d. 1522), who compiled all of the biographies of his predecessors into one collection and brought that medieval tradition of Ibadi prosopography to a close.
Keywords: Recension

Adam Gaiser, Shurāt Legends, Ibāḍī Identities: Martyrdom, Asceticism and the Making of an Early Islamic Community, Columbia: University of South Carolina Press, 2016, 223 pp. (including bibliography and index), ISBN 978-1-61117-676-6. - Francesca, Ersilia (Der Islam, 2019)
Keywords: Recension

Ziaka, Angeliki (Hg.):On Ibadism - Rebstock, Ulrich (Orientalistische Literaturzeitung, 2016)
Keywords: Recension

Ersilia, Francesca (Hg.): Ibadi Theology. Rereading sources and scholarly works. 2015. - Rebstock, Ulrich (Orientalistische Literaturzeitung, 2016)
Keywords: Recension

Cyrille Aillet (ed.): L’Ibadisme, une minorité au coeur de l’islam, thème sur la direction de Cyrille Aillet, Revue des Mondes Musulmans et de la Méditerranée, Série Histoire, Aix-en-Provence - Fierro, Maribel (Der Islam, 2016)
Keywords: Recension

AL-SALIMI, A., and W. MADELUNG (eds.) — Early Ibadi Literature. Abu l-Mundhir Bashir b. Muhammad b. Mahbub, Kitab al-Rasf fi l-Tawhid, Kitab al-Muharaba and Sira - Custers, Martin H. (Bibliotheca Orientalis, 2012)
Keywords: Recension

MURANYI, M. – The First Compendium of Ibadi Law. The Mudawwana by Abu Ghanim Bishr b. Ghanim al-Khurasani. - Custers, Martin H. (Bibliotheca Orientalis, 2019)
Keywords: Fiqh -- Libye -- 8e siècle; Recension

MADELUNG, W., and A. AL-SALIMI (eds.) – Ibāḍī Texts from the 2nd/8th Century. (M.H. Custers) - Custers, Martin H. (Bibliotheca Orientalis, 2019)
Keywords: Recension

EISENER, R. (ed.) – Today’s Perspectives on Ibadi History - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

AL-KHARUSI, K. – Āthār al-Rabīʿ b. Ḥabīb. Edition and Study - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

AL SALIMI, A., and E. STAPLES (eds.) – The Ports of Oman - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

AL SALIMI, A., and E. STAPLES (eds.) – Oman. A Maritime History - Custers, Martin H. (Bibliotheca Orientalis, 2018)
Keywords: Recension

Michalak-Pikulska, B. and R. Eisener (eds.) – Ibadi Jurisprudence. Origins, Developments and Cases - Custers, Martin H. (Bibliotheca Orientalis, 2016)
Keywords: Recension

FRANCESCA, E. (ed.) – Ibadi Theology. Rereading Sources and Scholarly Works - Custers, Martin H. (Bibliotheca Orientalis, 2016)
Keywords: Recension

WILKINSON, J.C. – Water and Tribal Settlement in South-East Arabia. A Study of the Aflāj of Oman. - Custers, Martin H. (Bibliotheca Orientalis, 2014)
Keywords: Recension

HOFFMANN-RUF, M., und A. AL SALIMI (Hrsg.) – Oman and Overseas. proceedings of the Inter- national Conference ‘The Ibadism of Oman - Its Overseas Development and its perception Over- seas’ held at Tübingen University, 16th-19th of May 2011. - Custers, Martin H. (Bibliotheca Orientalis, 2014)
Keywords: Recension

GAUBE, H., with contributions by A. AL SALIMI – The Ibadis in the Region of the Indian Ocean. Section One: East Africa - Custers, Martin H. (Bibliotheca Orientalis, 2014)
Keywords: Recension

PREVOST, V .- L'aventure ibadite dans le Sud tunisien (VIIle-xrne siècle). Effervescence d'une région méconnue. - Custers, Martin H. (Bibliotheca Orientalis, 2009)
Keywords: Recension

ZIAKA, A. (ed.) – On Ibadism. - Custers, Martin H. (Bibliotheca Orientalis, 2015)
Keywords: Recension

HOFFMANN-RUF, M. — Scheich Muhsin bin Zahran al-’Abri. Tribale Macht im Oman des 19. Jahrhunderts. - Custers, Martin H. (Bibliotheca Orientalis, 2010)
Keywords: Recension

CUSTERS, M. H.- Ibadi publishing activities in the East and in the West c. 1880-1960s. An attempt to an inventory, with references to related recent publications - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

CUSTERS, M. H.- Al-Ibadiyya. A bibliography. Volume 1: Ibadis of the Mashriq; Volume 2: Ibadïs of the Maghrib (incl. Egypt); Volume 3: Secondary literature - Sadgrove, Philip C. (Bibliotheca Orientalis, 2009)
Keywords: Recension

Al-Kharusi Kahlan: Āthār al-Rabīʿ b. Ḥabīb. Edition and Study - Tilier, Mathieu (Bulletin critique des Annales islamologiques, 2018)
Keywords: Recension

Daniel Panzac, La République de Venise et les Régences barbaresques au XVIIIe siècle. Un exemple de relation Nord-Sud en Méditerranée occidentale, Éditions Publisud, 2015. - Chiffoleau, Sylvia (Revue des mondes musulmans et de la Méditerranée, 2017)
Keywords: Recension

Daniel Panzac, La République de Venise et les Régences barbaresques au xviiie siècle. Un exemple des relations Nord-Sud en Méditerranée occidentale, édition établie, présentée et annotée par Salvatore Speziale, avant-propos de Michele Brondino, Paris, Publisud, 2015, 356 p. - Hocquet, Jean-Claude (Cahiers de la Méditerranée, 2016)
Keywords: Recension

Cohen-Tannoudji Denis (dir.), Entre orient et occident, Juifs et Musulmans en Tunisie, Paris, Éditions de l’éclat, 2007, 379 p. - Abécassis, Frédéric (Revue des mondes musulmans et de la Méditerranée, 2009)
Ce livre est le produit d’une rencontre, tenue à la Sorbonne en avril 2003, entre chercheurs français, tunisiens et israéliens à l’initiative de la Société d’histoire des Juifs de Tunisie. Le colloque s’est tenu sous le quadruple patronage de l’UNESCO, du CNRS, des ministères des Affaires étrangères et de l’Éducation nationale, en impliquant bien d’autres acteurs institutionnels. Sans qu’il n’y soit jamais fait référence, l’ouvrage, paru quatre ans plus tard, porte la marque du contexte dans ...
Keywords: Recension

L’ibadisme dans les sociétés de l’islam médiéval: Modèles et interactions: edited by Cyrille Aillet - Hoffman, Valerie J. (Islam and Christian–Muslim Relations, 2020)
Keywords: Recension

Oman: Politics and Society in the Qaboos State, by Marc Valeri. Columbia University Press, 2009. 284 pages. $70. - Kechichian, Joseph Albert (Middle East Policy, 2010)
Keywords: Recension

A Modern History of Oman: Formation of the State Since 1920By Francis Owtram (London: I. B. Tauris, 2004). 232 pp. Price HB £35.00. ISBN 1-86064-617-4 - Jones, Jeremy (Journal of Islamic Studies, 2006)
Keywords: Recension

Abdulrahman Al-Salimi and Wilferd Madelung: Early Ibāḍī Theology: Six kalām Texts by ‘Abd Allāh B. Yazīd Al-Fazārī. (islamic History and Civilization.) Cvi, 241 Pp. Leiden: Brill, 2014. €99. Isbn 978 90 04 27025 1. - Gaiser, Adam R. (Bulletin of the School of Oriental and African Studies, 2015)
Keywords: Fazārī, ʿAbd Allāh ibn Yazīd al-; Recension

Patricia CRONE and Fritz ZIMMERMANN: The, Epistle of Salim ibn Dhakwan. Oxford, 2001: Oxford University Press, xii, 407 pp. ISBN O 19 815265 5. £ 65.00. - Conrad, Lawrence (Der Islam, 2004)
Keywords: Recension

Les Mosquees Ibadites du Djebel Nafusa. Architecture, histoire et religions du nord-ouest de la Libye (VIIIe-XIIIe siecle). By Virginie Prevost. - Sjöström, Isabella (Libyan Studies, 2018)
Keywords: Recension

A Gateway to Hell, A Gateway to Paradise: The North African Response to the Arab Conquest. By ELIZABETH SAVAGE. Studies in Late Antiquity and Early Islam, vol. 7. Princeton: DARWIN PRESS, 1997. Pp. x + 206. $29.95. - Bonner, Michael (Journal of the American Oriental Society, 2000)
Keywords: Recension

PREVOST, Virginie, L'aventure ibadite dans le Sud tunisien (VIIIe-XIIIe siècle). Effervescence d'une région méconnue, Tuusula y Helsinki: Academia Scientiarum Fennica, "Humaniora 350", 2008, 479 págs., ilustraciones. - Viguerra Molins, Maria Jesus (Anaquel de Estudios Árabes, 2009)
Keywords: Recension

A History of Modern Oman Jeremy Jones and Nicholas Ridout Cambridge: Cambridge University Press, 2015 (301 Pages + Maps, Index) $94.99 (cloth) - Crouzet, Guillemette (Arab Studies Journal, 2016)
Keywords: Recension

Adam Gaiser, Muslims, Scholars, Soldiers. The Origin and Elaboration of the Ibadi Imamate Traditions, New York: Oxford University Press, 2010. 203 S., ISBN 0-19-973893-9, 978-0-19-973893-9 - Aillet, Cyrille (Der Islam, 2012)
Keywords: Recension

Mandana E. Limbert, In the Time of Oil: Piety, Memory, and Social Life in an Omani Town (Stanford, Calif.: Stanford University Press, 2010). Pp. 264. $65.00 cloth, $24.95 paper, 24.95 e-book. - Miller, Flagg (International Journal of Middle East Studies, 2011)
Keywords: Recension

The Essentials of Ibadi Islam. By VALERIE J. HOFFMAN. Modern Intellectual and Political History of the Middle East. Syracuse: SYRACUSE University PRESS, 2012. Pp. xii + 344. $39.95. - Francesca, Ersilia (Journal of the American Oriental Society, 2015)
Western scholars and students with an interest in the history of Ibädi Islam and Oman are no doubt familiar with the name and some of the extensive works of the author of the book under review, in which she resumes her previous research devoted to Ibädism in Oman and Zanzibar in the nineteenth and twentieth centuries. During repeated research stays in Oman over a decade Hoffman collected the material for the present volume, which, as she phrases it in the introduction, "is an attempt to introduce Ibädi Islamic theology to students and scholars of Islam, mainly through annotated translations of two basic Ibädi theological texts, in order to address the general unavailability of Ibädi texts to all but the most specialized scholars of Islam" (p. 4). The relative lack of interest in Ibädi theology may be partly because Ibädi religious literature is often obscure and difficult to understand. In fact, the oldest Ibädi theological literature is mainly fragmentary intra-community correspondence: letters (generally termed sira, pi. siyar) from imams and ulema with advice and/or explanations to the members about controversial religious and political issues. Moreover, according to European works from the last century, of which the older ones rely on only a few Ibädi sources, the distinctive nature of Ibädism seems to consist chiefly of a quietist political doctrine and of a religious puritanism. However, Ibädism presents a more complex reality. First of all, its sectarian nature is not so obvious. According to tradition, the Ibädi movement derives its name from cAbd Alläh Ibn Ibäd, who broke from Khäriji extremists in circa 65 A.H. (684/5) over the attitude to be adopted toward other Muslims. The Ibädis have been wrongly identified with the Khärijls by both Western scholars and non-Ibädi Muslim authors-Ibädis are instead very distant from them in political as well as religious matters. The connection between the two stems from the fact that most of the dissident Khärijis were from the Tamim tribe to which Ibn Ibäd also belonged. Moreover, proto-Ibädis were part of the Muhakkima movement of the early Khärijis, sharing with them the principle that the rule on earth belongs to God alone (la hukma ilia li-lläh). The Ibädi distinction from orthodox or Sunni Islam should be conceived in terms of internal Islamic diversity of doctrinal belief rather than in terms of their affiliation to Khärijism. As such the Ibädis are not a sect but a school (madhhab) that kept in close contact with the Sunni community and contributed to the general debate from which Islamic law and theology began to develop during the first two centuries in the heartland of the Muslim world, namely, Basra and Kufa, but also the Hijäz. Despite its antiquity, Ibädi Islam-and particularly Ibädi theology-remains little known and has often been misunderstood. To date the best-known monographs devoted to Ibädi theology in a European language are Studies in Ibädism by 'A. Kh. Ennami (Ph.D. diss., Cambridge Univ., 1971; [Benghazi]: Univ. of Libya, 1972; [Muscat] 22005) and Introduction a l'étude de l'ibadisme et de sa théologie by P. Cuperly (Algiers: Office des Publications Universitaires, 1984). This book by Valerie Hoffman seeks to amend the gap of three decades. Her main source is a brief and clear text intended as a primer for Ibâdï students of theology, al-cAqlda al-wahbiyya by Nâsir b. Sâlim b. cUdayyam al-Rawâhï (d. 1920), a prolific scholar better known in Oman as Abu Muslim al-Bahlânï. Unfortunately he died prematurely, leaving the work incomplete. Hoffman therefore also includes a translation of the passages of Kitab MaJalim al-dln by cAbd al-cAzïz al-Thamïnï al-Muscabï (d. 1808) dealing with predestination, a fundamental topic of Ibâdï theology that is omitted in al-Rawâhï's primer. Although it would be impossible to understand the early development of the movement and the doctrinal and political disputes over issues that led to its split into several subdivisions (firqa) without a reference to Ibädism's classical sources, I should emphasize the importance of including recent Ibâdï scholarship in an account on theology. Since theology played a role historically in creating sectarian identities and in defining and safeguarding Islamic belief, it is crucial to inquire about the theological discussions and debates among Ibâdîs during the nineteenth and twentieth centuries when the Ibâdï reform movement began to reconcile Islam and modernity. Through an analysis of modern Ibâdï religious literature, Hoffman sheds light on Ibâdï theological formulations on topics that differentiate Ibâdï doctrine from Sunni Islam, such as reward and punishment in the afterlife, free will and predestination, anthropomorphic description of God, the creation of the Quran, and so on. The theological tenets explicated by Hoffman are of great importance in understanding not only prevailing Ibâdï doctrine, but also their striving from the nineteenth century onward to avoid both Westernization and Islamic radicalism. Nevertheless, fundamental Islam remains an important part of Ibadism. Ibâdï ethical principles reveal a rigorous conception of life and faith. Sinful actions entail the loss of a state of purity and render the sinner unfit to participate in religious rites. This moral austerity leads the Ibâdîs to refute any kind of innovation, laxity, or modern idea and to interpret the ancient precepts in the most stringent fashion. Salvation can only be achieved through prayer, pious living, and hard work. Ibâdîs show a strong cohesion as a group outside of the mainstream; its dogmatic basis lies in the concepts of waläya and banda (association and dissociation), namely, the duty of friendliness toward individuals who fulfil the precepts of religion and, conversely, the duty of hostility against those who do not deserve to be called believers. The doctrine of waläya and banda has its counterpart in orthodox belief only as regards the general duty of solidarity with the faithful and hostility toward infidels. According to the general rule, true believers must declare beträgt from tyrants and their followers and they must not take any of them as wäll. A country governed by tyrants and unjust rulers must be declared a land of tyranny and injustice. In the early centuries of Islam, a serious threat to the exacting Ibâdï position was represented by MurjPites, who propounded the doctrine of suspended judgment on the fate of sinners in the afterlife and on the first fitna. This was wholly contrary to the Ibâdï view of TJthmän and cAlï and their rejection of the Umayyad dynasty. The contribution of MurjPism was crucial to Ibâdï development, for some MurjPï ideas penetrated the movement; they were propagated by Härün b. al-Yamän (fl. ninth century), causing a serious split in the Mashriqï Ibâdï community. He proposed a tolerant attitude to waläya and baräya, according kufr status only to those committing sins that deserved hadd punishment in this world and hell in the next. He recognized a middle way (manz.Ua bayna l-manzilatayn) for people committing sins that his predecessors, such as Abu Ayyub, considered to be major. Furthermore, Härün tied the faith to individual piety (taqwä) rather than to the strict interpretation of religious observances. On this topic, crucial for the understanding of Ibädism, Hoffman emphasizes a definite inconsistency between theory and practice in the modern Ibâdï sources. One would expect an intolerant attitude toward all those not deserving the status of "true believers," but al-Rawâhï's primer shows a high degree of tolerance toward non-Muslims (e.g., the British Colonial Office in Zanzibar) and toward nonIbâdï Muslims, who are treated like Ibâdîs where intermarriage and mutual inheritance are concerned. After tracing the history of the movement and delineating its distinctive teachings in the first part of the book (pp. 3-53), Hoffman turns the second part (pp. 55-237) over to the translation of al-Rawâhï's al-cAqlda al-wahbiyya and the third part (pp. 241-76) to the partial but valuable translation of al-Muscabï's Kitäb MaJälim al-dln. The volume concludes with a glossary, a biographical dictionary, references, and an index (pp. 279-344). The translations are generally convincing and competent. Al-Rawâhï was a great poet and mystic (his biography is on pp. 45-46) and the author of some works of prose including his cAqida, which owes its name to cAbd Allah b. Wahb al-Râsibï, one of the first Khârijî leaders, who was killed at the battle of Nahrawân. The cAqida synthesizes and popularizes Ibâdï doctrine by way of a dialogue between students and teacher in which the latter elucidates the Ibâdï principles of faith and discusses the doctrines of different Muslim schools (Sunni, Shici, Mu'tazilï, and Khârijî) as well as the differences between the North African and the Eastern (Oman and Zanzibar) Ibâdï communities. The particular importance of Hoffman's volume lies in the first translation into English of this important and interesting text. For the rest, The Essentials of Ibadi Islam is a basic introduction to Ibâdism, polished and well written, ideal for the graduate classroom or even the advanced undergraduate, and suitable for those wanting to understand Ibâdï doctrine and acquaint themselves with theological texts.
Keywords: Recension

Ibadi Theology: Rereading Sources and Scholarly Works. Edited by Ersilia Francesca. Studies on Ibadism and Oman, vol. 4. Hildesheim: Georg Olms, 2015. Pp. 331. €68. - Rodrigo, Adem (Journal of the American Oriental Society, 2018)
Keywords: Recension

Ibâdism: origins and early development in Oman - Hoffman, Valerie J. (Der Islam, 2014)
Keywords: Recension

L'Aventure Ibadite dans le Sud Tunisien: Effervescence d'une région méconnue (VIIIe-XIIIe siècle) - Ghazal, Amal N. (Der Islam, 2013)
Keywords: Nukkarisme; Recension

Reviewed Work: The Ports of Oman by Abdulrahman Al Salimi/Erich Staples - Hoffmann-Ruf, Michaela (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Islamic Law, Gender, and Social Change in Post-Abolition Zanzibar - Kapteijns, Lidwien (Islamic Africa, 2016)
Keywords: Recension; Zanzibar

Islamic Law, Gender, and Social Change in Post-Abolition Zanzibar, written by Elke E. Stockreiter, 2015 - Stiles, Erin E. (Islamic Law and Society, 2016)
Keywords: Recension; Zanzibar

Islamic Law, Gender, and Social Change in Post-Abolition Zanzibar, written by Elke E. Stockreiter - McMahon, Elisabeth (Journal of Religion in Africa, 2016)
Keywords: Recension; Zanzibar

Al Salimi, Abdulrahman and Staples, Eric: A Maritime Lexicon. Arabic Nautical Terminology in the Indian Ocean. English-Arabic Edition. Hildesheim/Zürich/New York: Georg Olms Verlag 2019. 641 S. m. 341 Abb. 4° = Studies on Ibadism and Oman. Vol. 11. Hartb. € 88,00. ISBN 978-3-487-15393-3. - Müller, Walter W. (Orientalistische Literaturzeitung, 2020)
Keywords: Recension

Early Ibāḍī Literature: Abu l-Mundhir Bashīr b. Muḥammad b. Maḥbūb Kitāb al-Raṣf fi l-Tawḥīd, Kitāb al-Muḥāraba and Sīra, by Abdulrahman al-Salimi and Wilferd Madelung (eds.) - Gaiser, Adam R. (Ilahiyat Studies, 2010)
Keywords: Recension

The Essentials of Ibāḍī Islam, by Valerie J. Hoffman - Salimi, Abdulrahman al- (Ilahiyat studies, 2013)
Keywords: Recension

Review of Oman. A Maritime History - Gemeinhardt-Buschhardt, Konstanze (Zeitschrift der Deutschen Morgenländischen Gesellschaft, 2020)
Keywords: Recension

Virginie Prevost: Les mosquées ibadites du Djebel Nafūsa. Architecture, histoire et religions du nord-ouest de la Libye (viiie/xiiie siècle). (Society for Libyan Studies Monograph, 10.) xxi, 232 pp. London: The Society for Libyan Studies, 2016. ISBN 978 1 900971 41 6. - Aillet, Cyrille (Bulletin of the School of Oriental and African Studies, 2018)
Keywords: Recension

The homecoming - Halberstadt, Ilona (Sight and Sound, 2001)
Keywords: Recension

The Essentials of Ibāḍī Islam by Valerie J. Hoffman (review) - Brown, Jonathan (Journal of Shi'a Islamic Studies, 2014)
Keywords: Recension

The Essentials of Ibadi Islam by Valerie J. Hoffman (review) - Timani, Hussam S. (Islamic Africa, 2014)
Keywords: Recension

Ibadi Muslims of North Africa: Manuscripts, Mobilization, and the Making of a Written Tradition by Paul M. Love, Jr. (review) - Propst, Amanda (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies, 2020)
Keywords: Recension

Book review: The Ibadis in the Region of the Indian Ocean. Section One : East Africa, written by Heinz Gaube - Prevost, Virginie (Arabica, 2015)
"Book review: The Ibadis in the Region of the Indian Ocean. Section One : East Africa, written by Heinz Gaube" published on 04 Mar 2015 by Brill.
Keywords: Recension

Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas - Prevost, Virginie (Arabica, 2015)
"Book review: Oman and Overseas éd. Michaela Hoffmann-Ruf et Abdulrahman al-Salimi, written by Oman and Overseas" published on 04 Mar 2015 by Brill.
Keywords: Recension

Ibadi Theology : Rereading Sources and Scholarly Works, written by Ersilia Francesca - Prevost, Virginie (Arabica, 2016)
Keywords: Recension

Ibadi Theology. Rereading sources and scholarly works, written by Ersilia Francesca - Demichelis, Marco (Oriente Moderno, 2016)
"Ibadi Theology. Rereading sources and scholarly works, written by Ersilia Francesca" published on 18 Nov 2016 by Brill.
Keywords: Recension

Āthār al-Rabīʿ b. Ḥabīb. Edition and Study, written by Kahlan Al-Kharusi, 2016 - Rebstock, Ulrich (Die Welt des Islams, 2018)
"Āthār al-Rabīʿ b. Ḥabīb. Edition and Study, written by Kahlan Al-Kharusi, 2016 " published on 16 Mar 2018 by Brill.
Keywords: Recension

Early Islamic Law in Basra in the 2nd/8th Century. Aqwāl Qatāda b. Diʿāma al-Sadūsī, edited by Al-Salimi, Abdulrahman - Francesca, Ersilia (Studi Magrebini, 2020)
Keywords: Recension

O[ma]n Ibadism and Modernity - Rebstock, Ulrich (Die Welt des Islams, 2020)
"O[ma]n Ibadism and Modernity" published on 27 May 2020 by Brill.
Keywords: Recension

The First Compendium of Ibadi Law. The “Mudawwana” by Abu Ghanim Bishr b. Ghanim al-Khurasani, written by Miklos Muranyi, 2018 - Rebstock, Ulrich (Die Welt des Islams, 2020)
Keywords: Fiqh -- Libye -- 8e siècle; Recension

Abdulrahman Al-Salimi and Eric Staples: A Maritime Lexicon: Arabic Nautical Terminology in the Indian Ocean. (Studies on Ibadism and Oman.) 641 pp. Hildesheim: Georg Olms Verlag, 2019. $98. ISBN 978 3 487 15393 3. - Bishara, Fahad Ahmad (Bulletin of the School of Oriental and African Studies, 2020)
Keywords: Recension

Eisener, Reinhard (Hg.): Today’s Perspectives on Ibadi History. Hildesheim/Zürich/New York: Georg Olms 2017. 349 S. m. Abb. 4° = Studies on Ibadism and Oman 7. Hartbd. € 68,00. ISBN 978-3-487-15152-6. - Rebstock, Ulrich (Orientalistische Literaturzeitung, 2019)
Keywords: Recension

Ahmed E. Souaiaia . Anatomy of Dissent in Islamic Societies: Ibadism, Rebelllion, and Legitimacy. New York: Palgrave Macmillan, 2013. xv + 228 pages, notes, bibliography, index. Cloth US$100.00 ISBN 978-1-13737-160-7. - Hoffman, Valerie J. (Review of Middle East Studies, 2016)
Keywords: Recension

Abdulrahman al-Salimi / Heinz Gaube (eds.): A New Collection Dedicated to Ibadism and Oman: A Review of the First Four Publications (2013–4) - Aillet, Cyrille (Der Islam, 2015)
Keywords: Recension

On Ibadism, written by Angeliki Ziaka - Jomier, Augustin (Arabica, 2017)
Keywords: Recension

John C. Wilkinson: Ibâḍism. Origins and Early Development in Oman. (Oxford Oriental Monographs.) xxxvii, 472 pp. Oxford: Oxford University Press, 2010. ₤90. ISBN 978 0 19 958826 8. - Ess, Josef van (Bulletin of the School of Oriental and African Studies, 2011)
Keywords: Recension

John C. Wilkinson, Ibâḍism: Origins and Early Development in Oman, Oxford Oriental Monographs (Oxford, U.K.: Oxford University Press, 2010). Pp. 500. $185.00 cloth. - Madelung, Wilferd (International Journal of Middle East Studies, 2012)
Keywords: Recension

Tunisie: La mémoire des Juifs de Djerba. Yaacov Bchiri - Weissenberg, Luc (Cahiers de musiques traditionnelles, 2001)
Keywords: Judaïsme -- Djerba; Recension

Kahlan Al-Kharusi (ed.): Āthār al-Rabīʿ b. Ḥabīb. Edition and Study. (Abhandlungen für die Kunde des Morgenlandes im Auftrag der Deutschen Morgenländischen Gesellschaft.) x, 172 pp. Wiesbaden: Harrassowitz, 2016. ISBN 978 3 447 10634 4. - Francesca, Ersilia (Bulletin of the School of Oriental and African Studies, 2020)
Keywords: Recension

Review of Dhows and the Colonial Economy of Zanzibar, 1860-1970 - Hoag, Heather J. (The International Journal of African Historical Studies, 2005)
Keywords: Recension

Spatial pattern of Islamic settlements of kampung Kauman Malang in the perspective of typical Mzab - Junara, Nunik; Sugeng, Triyadi S (IOP Conference Series: Earth and Environmental Science, 2018)
Keywords: Recension

Introduction à l’étude de l’ibāḍisme et de sa théologie, written by Pierre Cuperly - Di Tolla, Anna Maria (Annali dell'Istituto Universitario Orientale di Napoli, 2020)
Keywords: Recension

Les Ibadites. Mode de vie, organisation et patrimoine d’une minorité musulmane, conçu et coordonné par Virginie Prévost - Di Tolla, Anna Maria (Annali dell'Istituto Universitario Orientale di Napoli, 2019)
Keywords: Recension